Outcomes Comparison of Direct Stenting versus Pre Dilation in Percutaneous Coronary Intervention - Sajjad Ali, Iftikhar Ahmed, Farman Ullah, Muhammad Owais Khan, Muhammad Kashif Iltaf (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the outcomes of Direct Stenting (DS) versus pre-dilation in Percutaneous Coronary Intervention (PCI) by evaluating procedural time, fluoroscopy time, and clinical outcomes. Methodology: This retrospective study included 100 patients (50 in each group) who underwent PCI at the Department of Cardiology, Qazi Hussain Ahmed Medical Complex, Nowshera, from January 2022 to December 2022. Data on procedural times, fluoroscopy times, and clinical outcomes swere collected from patient records. Chi-square tests for categorical results and t-tests for continuous variables were used in the statistical study. Results: The results showed that DS resulted in a significantly shorter procedure time (23.4 ± 11.6 minutes) compared to pre-dilation (33.7 ± 14 minutes), with a p-value of 0.004. Fluoroscopy time was also significantly lower in the DS group (4.1 ± 2.5 minutes) compared to pre-dilation (6.7 ± 3.8 minutes), with a p-value of 0.002. No significant differences were observed in myocardial infarction (6% vs 8%, p = 0.67), revascularization needs (7% vs 9%, p = 0.72), side branch compromise (10% vs 8%, p = 0.72), or slow flow (5% vs 7%, p = 0.68) between the two groups. Conclusion: DS is a time-efficient and safe alternative to pre-dilation in PCI, offering reduced procedural and fluoroscopy times with similar clinical outcomes. More studies with larger populations are needed to validate these findings and explore long-term outcomes. Keywords: DS, pre-dilation, PCI, procedure time, fluoroscopy time.